2022
DOI: 10.1111/ggr.12423
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Re, Os, Ir, Ru, Pt, Pd Mass Fractions and 187Os/188Os Ratios of Organic‐Rich Geological Reference Materials

Abstract: At present, reported data for Re‐PGE mass fractions (in particular) and 187Os/188Os isotope ratios of organic‐rich reference materials (RMs) are rare, hampering the comparison of data quality between different laboratories. In this study, we measured the Re‐PGE (Os, Ir, Ru, Pt and Pd) mass fractions, as well as 187Os/188Os isotope ratios of five shale RMs, including USGS SGR‐1b (oil shale), SBC‐1 (marine shale), SCo‐2 (silty marine shale), ShTX‐1 (calcareous organic‐rich shale) and ShCX‐1 (calcareous shale), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 61 publications
(180 reference statements)
3
19
1
Order By: Relevance
“…Mixed 185 Re-190 Os and 191 Ir-99 Ru-194 Pt-105 Pd spike solutions calibrated as described in Wang et al were used. 18 Cation exchange columns were prepared using 30 ml Bio-Rad Econo-Pac columns (i.d. = 1.5 cm), packed with 20 ml AG 50W-X8 (200-400 mesh) resin.…”
Section: Reagents and Materialsmentioning
confidence: 99%
See 4 more Smart Citations
“…Mixed 185 Re-190 Os and 191 Ir-99 Ru-194 Pt-105 Pd spike solutions calibrated as described in Wang et al were used. 18 Cation exchange columns were prepared using 30 ml Bio-Rad Econo-Pac columns (i.d. = 1.5 cm), packed with 20 ml AG 50W-X8 (200-400 mesh) resin.…”
Section: Reagents and Materialsmentioning
confidence: 99%
“…Previous studies demonstrated that this RM is relatively homogenous in Re-Os-PGE mass fractions, 187 Os/ 188 Os and 187 Re/ 188 Os isotope ratios. 18,26 NIST RM 8505 is a Venezuelan crude oil certied for its vanadium concentration. Previous studies have comprehensively investigated its Re and Os mass fractions and Os isotopic compositions in whole oil, asphaltene separates (ASPH, n-alkane insoluble) and maltene separates (n-alkane soluble).…”
Section: Reagents and Materialsmentioning
confidence: 99%
See 3 more Smart Citations